The poison diary of 1996 part - 1 - Abd Razak, Dzulkifli (1997)
THE YEAR 1996 PROVED TO BE another year of surprises in terms of poisoning incidents, though not as shocking as that of the previous year. Nevertheless, 1996 continued to remind us that poisonous substances are very much part of our daily lives, both locally and globally. Below are the same of the monthtomonth highlights of what happened last year. These highlights are frequently accompanied by many more smaller events of no less worrying consequences.